Policy Options to Attract Nurses to Rural Liberia : Evidence from a Discrete Choice Experiment - Vujicic, Marko; Alfano, Marco; Ryan, Mandy; Wesseh, C. Sanford; Brown-Annan, Julie (World Bank, Washington, DC, 2013)
There is major geographic variation in nurse staffing levels in Liberia with the largest shortages in rural areas. A discrete choice experiment (DCE) was used to test how nurses and certified midwives in Liberia would respond to alternative policies being considered by the ministry of health and social welfare (MOHSW). The DCE methodology provides a quantitative estimate of how individuals value different aspects of their job. In Liberia we focused on six key job attributes: location, total pay, conditions of equipment, availability of transportation, availability of housing, and workload. Results were used to predict the share of nurses and certified midwives who would accept a job in a rural area under different schemes. Based on the DCE analysis there are four main actionable recommendations that emerge for improving recruitment and retention of nurses and certified midwives in rural areas of Liberia. First, the MOHSW should consider actively recruiting students from rural areas and exposing them to rural work conditions during their training. Second, the MOHSW should strongly consider increasing pay levels in rural areas as this is likely to be cost effective. Third, if for some reason financial bonuses are not feasible, the MOHSW should consider providing transportation to nurses and certified midwives in rural areas. Fourth, the MOHSW should reconsider its housing strategy. Providing newly constructed housing is not a cost effective policy according to the DCE study.